Upgrading of bio-oil via acid-catalyzed reactions in alcohols - A mini review - Hu, Xun; Gunawan, Richard; Mourant, Daniel; Hasan, M.D Mahmudul; Wu, Liping; Song, Yao; Lievens, Caroline; Li, Chun-Zhu (Elsevier, 2017)
© 2016 Elsevier B.V. Bio-oil is a condensable liquid produced from the pyrolysis of biomass, which can be upgraded to biofuels. Bio-oil is corrosive as it contains significant amounts of carboxylic acids, creating difficulties in handling of bio-oil and applications of bio-oil. Acid-treatment of bio-oil in alcohols is an upgrading method to transform the carboxylic acids in bio-oil into neutral esters. This study reviewed the recent progress in the research about the acid-catalyzed conversion of bio-oil in alcohols. The various catalytic processes for the acid treatment of bio-oil and the reaction network of some individual components of bio-oil during the upgrading were focused. The interactions among the main components of bio-oil during the acid-treatments were also discussed.